Drug resistance among infantile enteropathogenic Escherichia coli strains isolated in the United Kingdom. Issue 6340 (14th August 1982) - Gross, R J; Ward, L R; Threlfall, E J; King, H; Rowe, B
Abstract : Two hundred and thirty-two strains of Escherichia coli belonging to infantile enteropathogenic serotypes isolated in the United Kingdom during 1980 and 1981 were tested for resistance to 10 antimicrobial drugs. Resistance to one or more drugs was found in 134 (57.8%) of the strains, with resistance to sulphonamides, streptomycin, tetracycline, and ampicillin occurring most commonly. Resistance was transferable in 65 out of 104 resistant strains. These findings are a cause for concern because they indicate that the choice of treatment for severe illness is limited and suggest that a large pool of drug-resistant organisms exists in the community.